Defects in Actin Dynamics Lead to an Autoinflammatory Condition through the Upregulation of CXCL5 - Verdoni, Angela M. (Public Library of Science, 2008)
BACKGROUND: Destrin (DSTN) is a member of the ADF/cofilin family of proteins and is an important regulator of actin dynamics. The primary function of destrin is to depolymerize filamentous actin into its monomeric form and promote filament severing. While progress has been made in understanding the biochemical functions of the ADF/cofilin proteins, the study of an animal model for cells deficient for DSTN provides an opportunity to investigate the physiological processes regulated by proper actin dynamics in vivo. A spontaneous mouse mutant, corneal disease 1(corn1), is deficient for DSTN, which causes epithelial hyperproliferation and neovascularization in the cornea. Dstn(corn1) mice exhibit an actin dynamics defect in the cornea as evidenced by the formation of actin stress fibers in the epithelial cells. Previously, we observed a significant infiltration of leukocytes into the cornea of Dstn(corn1) mice as well as the upregulation of proinflammatory molecules. In this study, we sought to characterize this inflammatory condition and explore the physiological mechanism through which a loss of Dstn function leads to inflammation. METHODOLOGY/PRINCIPAL FINDINGS: Through immunofluorescent analyses, we observed a significant recruitment of neutrophils and macrophages to the Dstn(corn1) cornea, demonstrating that the innate immune system is spontaneously activated in this mutant. The inflammatory chemokine, CXCL5, was ectopically expressed in the corneal epithelial cells of Dstn(corn1) mice, and targeting of the receptor for this chemokine inhibited neutrophil recruitment. An inflammatory reaction was not observed in the cornea of allelic mutant strain, Dstn(corn1-2J), which has a milder defect in actin dynamics in the corneal epithelial cells. CONCLUSIONS/SIGNIFICANCE: This study shows that severe defects in actin dynamics lead to an autoinflammatory condition that is mediated by the expression of CXC chemokines.